ANALISIS PENGARUH STRES KERJA, WORK SUPPORT DAN KEPUASAN GAJI TERHADAP TURNOVER INTENTION PERAWAT (Studi Pada RSU Nirmala, Purbalingga) - Wahyudiana Mukti, Ulfa; Andriyani, Andriyani (Diponegoro Journal of Management, 2018)
The purpose of this research is to analyze the effect of work stress, work support, and salary satisfaction on nurse turnover intention (Study on RSU Nirmala Purbalingga).The data were collected through distribution of questionnaires to 95 nurses on RSU Nirmala Purbalingga using random sampling. The data test technique used in this research includes validity test, reliability test, classical assumption test, and multiple linear regression using SPSS software.The results of this study indicate that work stress has positive and significant effect on nurse turnover intention, work support has negative and significant effect on nurse turnover intention, and salary satisfaction has negative and significant effect on nurse turnover intention.